NPWP ENCRYPTION USES A COMBINATION OF ONE TIME PAD ALGORITHM AND EXCLUSIVE-OR OPERATION - Margaretha Pasaribu; Sherli Yurinanda; Niken Rarasati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Nomor Pokok Wajib Pajak (NPWP) is the 20 distinct code characteristics that are confidential only to the taxpayer when it comes to making tax transactions. The many tax payers who use NPWP others in their business activities make NPWP a very important aspect of maintaining confidentiality and the authenticity of their data. Therefore, solutions are needed that can be used to make the necessary information secure. Cryptography involves the secret science of code writing using certain mathematical models.The study discusses NPWP encryption using a combination algorithm One Time Pad (OTP) and an operation Exclusive-OR (XOR). The encryption process involves generating random numbers for an OTP algorithm, after which it is followed by an XOR operation. The key on XOR encryption is generated from an algorithm generating random numbers Blum Blum Shub. Encryption keys generated as much as the number of plaquic characters. The encryption keys used by each character would vary and not occur again. Therefore, ciphertext results from an encrypted process using an OTP algorithm and an XOR operation more complicated and more difficult to decipher by crypts.